The Development Learning Video of Cube And Cuboid for Deaf Students in the 3RD Grade of Middle School - Pramita Respati; Marhan Taufik; Agung Deddiliawan Ismail (MEJ (Mathematics Education Journal), 2018)
This research was aims to develop video instructional media of cube andcuboid for deaf students. The background of doing this research instructionalmedia is not only required by means of the normal students, but it is neededby the students who have special needs like deaf students also. Observationresult addresses that the deaf students are inclined to be slow in catching thematerials are given due to the lack of media, difficulty in imagining cube andcuboid, and forget the materials are given. In accordance with the students'characteristics and needs, it requires the visual-based media. This researchtypically employed research and development method. The result ofvalidation based on the assessment of media practitioner with the scalestarting from 0 to 5 was 4.42, and material practitioner from 0 to 5 was 4. Theresult of validator's assessment demonstrated that this instructional media canbe available to use. The result of students' response in using this instructionalmedia was 74.5 %. It revealed that students' response to this instructionalmedia was good. This research has added the Sistem Isyarat BahasaIndonesia (SIBI), and accordance with the characteristics of deaf students andalso has added animations from the Cabri3D software to help studentsobserve the shape and characteristics of the building blocks and cubes